2014
DOI: 10.5507/bp.2013.095
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of exercise-induced heart failure with normal ejection fraction in post-heart transplant patients

Abstract: Aim. Post-heart transplant patients are at increased risk of diastolic dysfunction. The aim of this study was to assess the prevalence of isolated only exercise-induced heart failure with normal ejection fraction (HFNEF) in heart transplant recipients. Methods and Results. To determine pulmonary capillary wedge pressure (PCWP) at rest and during exercise, 81 patients after orthotopic heart transplantation with normal left ventricular ejection fraction (LVEF) underwent exercise right heart catheterization with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…As Meluzin et al reported 10 —16% of HTx subjects had signs of diastolic dysfunction in rest conditions (14.6% in this study), but other 58% showed signs of diastolic impairment in stress conditions 10 . While the difference in PTT was not significant, PTTc, PTT_S and PTTc_S were significantly lower in the CCS group than the HTx_A subgroup, which follows our assumption.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…As Meluzin et al reported 10 —16% of HTx subjects had signs of diastolic dysfunction in rest conditions (14.6% in this study), but other 58% showed signs of diastolic impairment in stress conditions 10 . While the difference in PTT was not significant, PTTc, PTT_S and PTTc_S were significantly lower in the CCS group than the HTx_A subgroup, which follows our assumption.…”
Section: Discussionsupporting
confidence: 50%
“…PTT has already shown to be increased in both heart failure with reduced and preserved ejection fraction 6 , 9 . As previously published by Meluzin et al 10 , by pulmonary capillary wedge pressure acquired by right heart catheterization, 16% of patients after heart transplant (HTx) showed signs of diastolic dysfunction in rest condition, but in stress condition, another 58% showed these signs 10 . Therefore, we hypothesise that in a population after HTx, the stress biomarkers will be prolonged compared to a group of patients without any signs of systolic or diastolic function impairment.…”
Section: Introductionmentioning
confidence: 75%
“…Of the 30 patients with evidence of HFNEF, 6 (20%) had only exercise-induced HFNEF. In an invasive study of patients after orthotopic heart transplantation with normal LVEF, the same group of researchers 10 analyzed the response of pulmonary capillary wedge pressure (PCWP) to submaximal exercise. Of the 81 patients, 21 (26%) had no evidence of HFNEF (PCWP at rest < 15 mmHg, maximal PCWP was elevated.…”
Section: Prevalence and Clinical Importance Of Isolated Only Exercismentioning
confidence: 99%